Last interglacial (MIS 5e) sea level proxies in the glaciated Northern Hemisphere - Dalton, April S.; Gowan, Evan J.; Mangerud, Jan; Möller, Per; Lunkka, Juha P.; Astakhov, Valery (Zenodo, 2022)
This dataset contains known preserved last interglacial (Marine Isotope Stage 5e - 130-115 ka) sea level proxies in glaciated regions of North America and Europe, including Greenland and Iceland. We have excluded deposits that show evidence of glaciotectonism. In total there are 88 sea level proxies in this dataset. The sea level proxies have been dated using electron spin resonance, U-series, amino acid racemization, luminescence and radiocarbon techniques. In many cases, fossil assemblages and pollen records that indicate warmer-than-present conditions provide support for a last interglacial assignment. : Version 1.02 fixes an error in the coordinates for the site at Mertuanoja